Prevalence and treatment patterns of erectile dysfunction and hypogonadism in men with spina bifida: a retrospective study - Fortingo, Nyemkuna; Sandhu, Manpreet; Greear, Garrick; Hsieh, Tung-Chin; Horns, Joshua; Das, Rupam; Hotaling, Jim; Santiago-Lastra, Yahir (Frontiers in Urology, 2025)
ObjectivesTo characterize the estimated prevalence and treatment patterns of erectile dysfunction and hypogonadism in men with spina bifida through a large claims database.MethodsThis retrospective claims study used the MarketScan® databases from 2008 to 2017 to compare prevalence estimates for erectile dysfunction and hypogonadism in men with spina bifida to those in men without spina bifida and to describe treatment patterns in this cohort.ResultsThe estimated prevalence of erectile dysfunction and hypogonadism in men with spina bifida was 7.83% and 7.71%, respectively. Men with spina bifida exhibit high rates of smoking and metabolic comorbidities but are diagnosed less frequently with erectile dysfunction when controlling for age and metabolic comorbidities than men without spina bifida. Most men with spina bifida and erectile dysfunction (66.6%) or hypogonadism (77.4%) do not receive treatment. However, a diagnosis of spina bifida did not appear to affect the likelihood of treatment for either condition on multivariate analysis.ConclusionsMen with spina bifida are known to be at high risk for erectile dysfunction but may be diagnosed or treated less frequently than age and disease-matched men without spina bifida. Hypogonadism is diagnosed more frequently in men with spina bifida, which is a new finding that warrants further investigation. Most men with SB and either ED or HG do not receive treatment. The results suggest there is potential for improving care delivery for sexual health issues in men with spina bifida.